Eksplorasi Pengaruh Teknologi Kecerdasan Buatan Ter-hadap Efisiensi dan Produktivitas Pegawai di RSUD Dr. Soegiri Lamongan - Eka Ainur Rohmah; Rudi Wibowo; Jennifer Farihatul Bait; Suyitno Suyitno (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to explore the impact of the application of artificial intelligence (AI) technology on the efficiency and productivity of employees at Dr. Soegiri Lamongan Hospital. With the development of AI technology in the healthcare sector, this research is important to understand how this technology affects the quality of work of employees as well as operational productivity in hospitals. The method used was a descriptive qualitative approach with data collection through semi-structured interviews with 10 informants consisting of medical, administrative, and managerial employees. Data analysis was carried out using thematic analysis techniques to identify key patterns and themes in the interview data. The results of the study show that the application of AI at Dr. Soegiri Lamongan Hospital increases employee productivity by speeding up administrative and medical processes, as well as allowing employees to focus more on more complex tasks. Although some employees expressed concerns about job replacement, most felt more supported and efficient with the help of this technology. These findings contribute to the literature on AI adoption in the healthcare sector, by showing that AI can improve work efficiency without compromising employee psychological well-being. The conclusion of the study is that AI has great potential to improve productivity and efficiency in hospitals, with a positive impact on employee well-being. The study suggests that hospitals provide more intensive training and managerial support in implementing this technology, and proposes further research to explore more in-depth psychological factors related to the application of AI in the healthcare sector.